2020
DOI: 10.1016/j.ijso.2020.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesic efficacy of caudal tramadol added to bupivacaine compared to bupivacaine alone for pediatric elective infra umbilical surgery at Tikur Anbessa Specialized Hospital, Ethiopia, a prospective cohort study

Abstract: Background: Caudal epidural analgesia is one of the most popular reliable, safe and commonly performed regional blocks in pediatric patients undergoing lower abdominal and lower limb surgery. Various adjuvants such as opioids or α2 agonists are being used to improve the quality and duration of caudal analgesia. Addition of Tramadol to local anesthetics has been noted to prolong the duration of analgesia after surgery. Objective: To assess the efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…These findings were comparable to the previous studies. [11,12] During the first 24 hours, we noticed a reduced pain score in the bupivacaine-tramadol group as compared to group II with p value <0.002. When it comes to postoperative analgesia, the bupivacaine-tramadol group had much longer analgesia durations and a significantly lower need for rescue analgesia with p value <0.003.…”
Section: Discussionmentioning
confidence: 78%
“…These findings were comparable to the previous studies. [11,12] During the first 24 hours, we noticed a reduced pain score in the bupivacaine-tramadol group as compared to group II with p value <0.002. When it comes to postoperative analgesia, the bupivacaine-tramadol group had much longer analgesia durations and a significantly lower need for rescue analgesia with p value <0.003.…”
Section: Discussionmentioning
confidence: 78%
“…A recent study conducted by Angasa et al (2020) [18] in children aged 1-14-year old undergoing elective infraumbilical surgery received caudal block with bupivacaine 0.25% 1 mL/kg and bupivacaine 0.25% 1 mL/kg with tramadol 1 mg/kg. The mean pain score was lower in (BT) group with a statistically significant difference at 4 th , 8 th , and 12 th h post-operatively with p=0.018, 0.002, and 0.041, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various bupivacaine supplements have been used in many paediatric surgeries to increase the duration and quality of pain relief. Addition of tramadol to bupivacaine resulted in a dose-dependent upsurge in analgesia postoperatively [16][17] . This study showed a clinically and statistically substantial period of postoperatively pain reduction.…”
Section: Discussionmentioning
confidence: 99%